A Critical Analysis of Minority Protection under Ottoman Rule - Ali Muhammad Bhat (Maklumat: Journal of Da'wah and Islamic Studies, 2025)
In the late years of the 14th century people across the globe and Europe in particular believed in exclusive social structure based on uni-cultural values. At this conjuncture of history a new Muslim caliphate based on dynastic rule “the Ottoman Empire” emerged on the map of the world. This empire has two broad categories of people consisting of two groups Muslims and non-Muslims. Religion was the decisive factor in describing the statute of people under the Ottoman Empire. There were ethnic groups too under the Ottomans, all these groups were protected without any discrimination based on ethnicity, religion etc. All these groups were given full protection under the Ottoman legal system derived from Shari’ah. All non-Muslims enjoyed reasonable freedom under the course of law. The major significance of this paper is to bridge the gap/gulf which exists in the minds of general reading classes to facilitate peace and harmony between different communities across the globe.